2008
DOI: 10.3324/haematol.13524
|View full text |Cite
|
Sign up to set email alerts
|

The first deletion mutation in the TSP1-6 repeat domain of ADAMTS13 in a family with inherited thrombotic thrombocytopenic purpura

Abstract: analysis identified a homozygous deletion of nucleotides 2930-2935 (GTGCCC) in exon 23 of ADAMTS13 in the 2 probands, but also in one asymptomatic sibling. 13 In order to explain the patients' phenotype, we then studied the mechanistic effect of the deletion by means of expression studies in mammalian cells. Design and Methods PatientsTwo South Iranian patients (2 brothers), off-spring of first cousins, were affected by chronic recurrent TTP that first developed during adulthood (Figure 1). Patient II:2, a 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
(38 reference statements)
5
12
0
Order By: Relevance
“…In agreement with this finding, the report of Palla et al 15 shows that the recombinant 2930-2935del GTGCCC mutant protein has normal specific activity. On the other hand this mutation, by substituting the C977 with a W, probably alters the folding of the protease by disrupting a disulphide bond within the sixth TSP1 domain.…”
Section: -14supporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with this finding, the report of Palla et al 15 shows that the recombinant 2930-2935del GTGCCC mutant protein has normal specific activity. On the other hand this mutation, by substituting the C977 with a W, probably alters the folding of the protease by disrupting a disulphide bond within the sixth TSP1 domain.…”
Section: -14supporting
confidence: 80%
“…Only 15 mutations have been observed in homozygous form, including the one described in this issue of the journal by Palla et al, 15 who found a homozygous deletion of nucleotides 2930-2935 in exon 23 of ADAMTS13 in a South Iranian family. Interestingly, the deletion does not result in a frameshift and in protein interruption but it causes the replacement of C977 by a W and the deletion of A978 and R979 in the sixth TSP1 repeat domain where no mutations had so far been described.…”
mentioning
confidence: 95%
“…Of 18 patients, 10 had previously been screened for ADAMTS13 mutations by our groups (Table 1) (16,17,19,20,25,26). Here we identified the genetic ADAMTS13 defect in the other 8 patients (R002, F1518#728, F1519#728, F1627#873, F1628#873, F769#239, F1116#239, and R564).…”
Section: Mutation Screeningmentioning
confidence: 69%
“…The v aria nts p.V88 M, p .Q9 7f sX31 , p.C9 77 W +A978_R979del, p.R1123C, p.R1219W, p.G1239V, and p.E1382RfsX6 were previously described and functionally characterized by our groups (Table 3) (19,20,25). The p.R1060W has already been expressed by Camilleri (27) and Tao (28) and colleagues; however, these investigators reported different levels of secretion (,5% and 11.4%, respectively) and activity (fully active and 35% active, respectively).…”
Section: Functional Studies On Radamts13 Mutantsmentioning
confidence: 99%
“…42 A deletion mutation in the TSP1 sixth repeat of ADAMTS13 was identified in a family with hereditary TTP. 43 Furthermore, a homozygous mutation (W688X) found in a patient with hereditary TTP, which truncates ADAMTS13 4 amino acids after the spacer domain, was reported to have comparable activity to catalyze VWF73 peptides and predenatured VWF with wild-type ADAMTS13 but exhibited much less activity in cleaving native VWF under fluid shear stress. 44 Finally, autoantibodies against the TSP1 second to eighth repeats and the CUB domains of ADAMTS13 were identified in many patients with acquired TTP, although the functional consequence of these anti-ADAMTS13 IgGs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%